Pengembangan Media E-book Materi Kata Benda dan Kata Sifat Berbasis Metode Suku Kata Kelas II SD - Adiliyah; Hevitria; Arrosyad, M. Iqbal (UNIB Press, 2025)
This research is motivated by students' difficulties in beginning reading. Some students face challenges in recognizing and pronouncing syllables, while teachers still rely on printed textbooks for instruction. Therefore, there is a need for supporting media such as e-books to facilitate students' beginning reading skills. The study aims to develop a syllable method-based e-book focusing on nouns and adjectives that is valid, practical, and has potential effectiveness.This research is a Research and Development (R&D) study using the 4D development model, which consists of four stages: Define, Design, Develop, and Disseminate. Data collection techniques included questionnaire and tests. The subjects of this research were teachers and 33 students of class II A at SD Negeri 30 Pangkalpinang. The data analysis employed normality tests and paired sample t-tests. Based on the validator's assessment, the material expert scored 100% (Very Valid), and the media expert obtained an average score of 98.67% (Very Valid). The small-scale trial results showed 100% (Very Practical), the large-scale trial achieved 100% (Very Practical), and the teacher response questionnaire obtained 96% (Very Practical). The results of the paired sample t-test showed a significance value of 0.000 < 0.05, indicating a significant difference before and after using syllable-based e-book media for Noun and Adjective materials in class II of Elementary School.